What is the biggest motivator for 10 th-graders when learning programming? Case study in Vietnam - Tran Van, Hung; Thi, Hoa Nguyen; Ly Anh, Kiet Tran; Ba Tuan, Kiet Nguyen (Social sciences & humanities open, 2025)
Motivation is one of the important elements in the learning process, particularly for complex subjects like programming, which demand consistent engagement and strong problem-solving abilities. Grasping the nuances of student motivation is essential for educational researchers and practitioners dedicated to crafting more effective and engaging learning environments. This study examines four pivotal factors influencing 10th-grade students' motivation to learn programming in Da Nang, Vietnam: family influence, teacher influence, learning environment, and self-influence. By exploring these dimensions, we aim to propose actionable strategies that educators and parents can implement to foster a supportive and motivating educational atmosphere. Our analysis, conducted using SPSS24 and Structural Equation Modeling (SEM), highlighted that self-influence, family influence, learning environment, and teaching influence significantly drive student motivation. Key metrics include a Kaiser-Meyer-Olkin (KMO) value of .803, Cronbach's Alpha values exceeding 0.6, a Comparative Fit Index (CFI) of 0.946, Tucker-Lewis Index (TLI) of 0.932, and a Root Mean Square Error of Approximation (RMSEA) of 0.056. Additionally, ANOVA results with a significant value of .000 < .005 confirms that the independent variables positively impact students' motivation. These findings are valuable for educators, especially those involved in programming instruction at both high school and university levels.